A Case Study on How the Team Leaders in the Chinese University Lead Their Teams: From the Perspective of LMX - Cui, Xuanwei (Technium Social Sciences Journal, 2022)
The purpose of the current study aims to explore the leadership of the team leaders in a Chinese university from the perspective of Leader-Member Exchange (LMX). To fill this gap in the literature, the current study used a qualitative case-study method examining the factors that affect LMX at a Chinese university and the dimensions of LMX at a Chinese university. What emerged from the data was that: (1) all three participants considered followers’ personalities an essential factor affecting the relationship between a leader and their followers; (2) the matching between leaders and followers in their abilities, efforts, and personal aspirations is an essential factor affecting the relationship between leaders and followers; (3) leaders’ prior familiarity with followers is a critical factor affecting the relationship between leaders and followers; (4) the dimensions of leadership in the Chinese cultural context include mutual emotional support, trust, face, loyalty, commitment, and dedication; (5) there exists an element of paternal relationship in terms of the relationship between a leader and their followers in the Chinese culture.